2023
DOI: 10.1186/s10194-023-01603-3
|View full text |Cite
|
Sign up to set email alerts
|

PACAP6-38 improves nitroglycerin-induced central sensitization by modulating synaptic plasticity at the trigeminal nucleus caudalis in a male rat model of chronic migraine

Abstract: Aims Chronic migraine (CM) is a common neurological disorder with complex pathogenesis. Evidence suggests that pituitary adenylate cyclase-activating peptide (PACAP) induces migraine-like attacks and may be potential a new target for migraine treatment, but the therapeutic results of targeting PACAP and its receptors are not uniform. Therefore, the aim of this study was to investigate the regulatory effect of PACAP type I receptor (PAC1R) antagonist, PACAP6-38, on nitroglycerin (NTG)-induced ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The study showed that PACAP and PACAP type 1 receptor (PAC1R) expression were significantly raised in the Sp5C after repeated nitroglycerin injections. Therefore, the synthesis of BDNF rose when synaptic activity increased, indeed BDNF expression levels significantly increased after nitroglycerin injection, and the PAC1R antagonist, PACAP6-38, reversed the effects [106]. These results indicated that PACAP6-38 was capable of improving synaptic transmission and neuronal activation involving BDNF, the extracellular signal-regulated kinase, and the cAMP response element-binding protein (BDNF-ERK-CREB) pathway in chronic migraine rats [106].…”
Section: Neuropathic Orofacial Pain and Migraine Pain Modulationmentioning
confidence: 93%
See 2 more Smart Citations
“…The study showed that PACAP and PACAP type 1 receptor (PAC1R) expression were significantly raised in the Sp5C after repeated nitroglycerin injections. Therefore, the synthesis of BDNF rose when synaptic activity increased, indeed BDNF expression levels significantly increased after nitroglycerin injection, and the PAC1R antagonist, PACAP6-38, reversed the effects [106]. These results indicated that PACAP6-38 was capable of improving synaptic transmission and neuronal activation involving BDNF, the extracellular signal-regulated kinase, and the cAMP response element-binding protein (BDNF-ERK-CREB) pathway in chronic migraine rats [106].…”
Section: Neuropathic Orofacial Pain and Migraine Pain Modulationmentioning
confidence: 93%
“…Therefore, the synthesis of BDNF rose when synaptic activity increased, indeed BDNF expression levels significantly increased after nitroglycerin injection, and the PAC1R antagonist, PACAP6-38, reversed the effects [106]. These results indicated that PACAP6-38 was capable of improving synaptic transmission and neuronal activation involving BDNF, the extracellular signal-regulated kinase, and the cAMP response element-binding protein (BDNF-ERK-CREB) pathway in chronic migraine rats [106]. The BDNF-ERK-CREB pathway is fundamental for neuronal survival, synapses, and synaptic plasticity and it is also involved in cognitive impairment [107,108].…”
Section: Neuropathic Orofacial Pain and Migraine Pain Modulationmentioning
confidence: 95%
See 1 more Smart Citation
“…In animal models, PACAP has been shown to play a role in trigeminal sensitization, which is the process by which nociceptive signals become amplified and persistent, leading to chronic pain [137]. Studies have also found that PACAP is involved in the activation of inflammatory pathways in the trigeminal nerve, further contributing to pain and inflammation [138].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…In animal models, PACAP has been shown to play a role in trigeminal sensitization, which is the process by which nociceptive signals become amplified and persistent, leading to chronic pain [131]. Studies have also found that PACAP is involved in the activation of inflammatory pathways in the trigeminal nerve, further contributing to pain and inflammation [132].…”
Section: Preclinical Studiesmentioning
confidence: 99%